Tunisia : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2012)
The Central Bank of Tunisia's (CBT) liquidity support contributed to rapid credit growth in Tunisia and an uptick in inflation. The Tunisian economy is expected to recover gradually. Banking sector vulnerabilities are much higher, and stress tests indicate that the banking sector may face large recapitalization needs. Improving financial intermediation efficiency, antimoney laundering, and combating the financing of terrorism is required. A comprehensive capital market reform is needed to support long-term investment. Banking sector reform should improve access to finance for individuals, and small and medium enterprises.